Returning to play after prolonged training restrictions in professional collision sports - Stokes, K. A.; Jones, B.; Bennett, M.; Close, G. L.; Gill, N.; Hull, J. H.; Kasper, A. M.; Kemp, S. P. T.; Mellalieu, S. D.; Peirce, N.; Stewart, B.; Wall, B. T.; et al. (International Journal of Sports Medicine, 2020)
The COVID-19 pandemic in 2020 has resulted in widespread training disruption in many sports. Some athletes have access to facilities and equipment, while others have limited or no access, severely limiting their training practices. A primary concern is that the maintenance of key physical qualities (e. g. strength, power, high-speed running ability, acceleration, deceleration and change of direction), game-specific contact skills (e. g. tackling) and decision-making ability, are challenged, impacting performance and injury risk on resumption of training and competition. In extended periods of reduced training, without targeted intervention, changes in body composition and function can be profound. However, there are strategies that can dramatically mitigate potential losses, including resistance training to failure with lighter loads, plyometric training, exposure to high-speed running to ensure appropriate hamstring conditioning, and nutritional intervention. Athletes may require psychological support given the challenges associated with isolation and a change in regular training routine. While training restrictions may result in a decrease in some physical and psychological qualities, athletes can return in a positive state following an enforced period of rest and recovery. On return to training, the focus should be on progression of all aspects of training, taking into account the status of individual athletes.